Comparative Analysis of The Performance of Sharia Banks and Conventional Banks in Indonesia - Rendra Arief Hidayat; Indah Shofiyah; Hendra Hendra (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2022)
This paper examines the comparative performance of sharia banks and conventional banks for the period 2010-2020. The financial performance itself is seen from 3 aspects, namely efficiency, asset quality, and stability. Based on previous empirical research, the indicators used to measure efficiency are BOPO, asset quality with NPF (sharia banks) and NPL (conventional banks), and stability with Z scores. This research was conducted at sharia banks and conventional banks in the period 2010-2020 and used secondary data. The sample used was selected by purposive sampling. The data used in this study were obtained from financial statements collected and published through the Otoritas Jasa Keuangan (OJK) website www.ojk.go.id, the Osiris database, and the website of each bank that was used as a research sample and tested using two different statistical techniques average (independent sample test). The results of this study indicate that the rapid development of sharia banks compared to conventional banks in the post-crisis period was followed by the consistency of performance (better than conventional banks) as shown in the crisis period